2020
DOI: 10.1007/s10508-020-01755-2
|View full text |Cite|
|
Sign up to set email alerts
|

LGBQ+ Self-Acceptance and Its Relationship with Minority Stressors and Mental Health: A Systematic Literature Review

Abstract: Many individuals who identify as lesbian, gay, bisexual, queer, and with other non-heterosexual orientations (LGBQ+) experience stigma, prejudice, and/or discrimination because of their sexuality. According to minority stress and identity development theories, these experiences can contribute to difficulties with self-acceptance of sexuality. Lower self-acceptance is considered a risk factor for adverse mental health outcomes. The current review aims to investigate whether self-acceptance of sexuality is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 67 publications
(175 reference statements)
0
27
0
3
Order By: Relevance
“…These attitudes influence a higher level of internalized homonegativity, resulting in less acceptance of their bi identity [58]. Higher levels of positive identity in gay people have been previously highlighted in comparison to their bisexual peers [59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 96%
“…These attitudes influence a higher level of internalized homonegativity, resulting in less acceptance of their bi identity [58]. Higher levels of positive identity in gay people have been previously highlighted in comparison to their bisexual peers [59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 96%
“…A systematic review of studies involving both LGBTQ youth and adults has similarly found that greater social support and acceptance are associated with greater LGBTQ identity pride and sexuality self-acceptance. 30 Previous research has found that family support may be particularly important for identity pride and mental health among LGBTQ youth since youth often spend a substantial amount of time with their family. 31,32 However, other sources of support may also play a role in LGBTQ youths' mental health, such as support from teachers.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of such support, individuals may develop negative self-identity and, possibly, depression. Also, people who did not report a sexual identity may not feel comfortable owning and accepting their gender identity, which is why they may be depressed (Camp et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This conceptual understanding and findings can aid psychologists, social workers, mental health professionals, community organizers, and grassroots leaders to become aware of the effect that multiple socially marginalized statuses and subordinate identities can have on their mental health. For example, since lack of self-acceptance and social support can lead to depression, mental health providers should focus on strengthening social resources in addition to self-esteem (Camp et al, 2020). Religious conflict can also be a focal area of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation